Comparison between unified communication centre and manual method / Rafidah Othman - Othman, Rafidah (2004)
The purpose of this project is to make comparison between Unified Communication Centre and manual method. Unified Communication is the place that all communication such as e-mail, fax and phone put in one location (inbox). It is the product which using the Unified Communication Centre Web-based. To achieve this project some testing had been done by some of the comparison between the traditional technologies that using the fax, email and phone and using the Unified Communication Centre Services web-based. It needs the user subscriber to the Internet service provider (ISP) which using a Celcom.net as a testing. The benefit doing this project is to make the user know about communication technology that has always change from time to time. This project also gives some recommendations to make this improvement and can be continued to other student who interested in communication technology. Beside that, the Unified Communication also has an advantages and features which it give the user easy to manage their communication.